Congenital anomalies in a tertiary care hospital in North East region, India - Praneshwari, R. K.; Singh, N. Nabakishore; Devi, Akoijam Tamphasana; Priya, Jyoti; Singh, L. Ranjit (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Congenital anomalies are important cause of morbidity and mortality in newborns and are defined as structural and functional abnormalities including metabolic disorders present at birth. These defects are of prenatal origin resulting from defective embryogenesis or intrinsic abnormalities in the process of development and are associated with various risk factors. Methods: Our study is a cross sectional study done at Regional Institute of Medical Sciences, Imphal over period of 3 years from January 2015 to December 2017. Aim of study was to find out incidence of congenital anomalies and proportions of different types of congenital anomalies. Outcome was studied in relation to maternal age, religion, parity, and gestational age, sex of the baby, outcome and sex of the baby. Results: Total numbers of congenital anomalies were 257 babies out of 29879 births giving the incidence of 0.86%. Most common congenital anomalies in this study are musculoskeletal followed by craniospinal, genitourinary, cardiovascular and gastrointestinal. It was more common in preterm babies and parity 1-3, more common in 21-30 years of maternal age. Consanguinity was seen in 7 out of 257 patients. Conclusions: Congenital malformations are a major cause of still births and infant mortality. Targeted scan should be done at 18-20 week to find out anomalies and reduce the prevalence. There should be widespread education in the community regarding the common congenital malformations, their outcomes and possible available mode of treatment